2016
DOI: 10.1038/srep21921
|View full text |Cite
|
Sign up to set email alerts
|

From Flexible and Stretchable Meta-Atom to Metamaterial: A Wearable Microwave Meta-Skin with Tunable Frequency Selective and Cloaking Effects

Abstract: This paper reports a flexible and stretchable metamaterial-based “skin” or meta-skin with tunable frequency selective and cloaking effects in microwave frequency regime. The meta-skin is composed of an array of liquid metallic split ring resonators (SRRs) embedded in a stretchable elastomer. When stretched, the meta-skin performs as a tunable frequency selective surface with a wide resonance frequency tuning range. When wrapped around a curved dielectric material, the meta-skin functions as a flexible “cloakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 51 publications
(58 reference statements)
0
50
0
1
Order By: Relevance
“…In 2015, Alam et al suggested an 8 × 8-mm 2 "hexagonal" DNG metamaterial, where the bandwidth was 1.75 GHz (from 1.68-3.43 GHz) and 0.96 GHz (from 5.04-6.0 GHz) [4]. In 2016, Yang et al demonstrated a "ring-shaped" 5 × 5-mm 2 meta-atom for wearable, flexible and stretchable microwave meta-skin, with clocking effects from 8-13 GHz and an effective medium ratio of six [5]. In 2016, Du et al presented a left-handed metamaterial created by the combination of ferrite sheets and dielectric rods to investigate the electromagnetic properties for X-band applications [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2015, Alam et al suggested an 8 × 8-mm 2 "hexagonal" DNG metamaterial, where the bandwidth was 1.75 GHz (from 1.68-3.43 GHz) and 0.96 GHz (from 5.04-6.0 GHz) [4]. In 2016, Yang et al demonstrated a "ring-shaped" 5 × 5-mm 2 meta-atom for wearable, flexible and stretchable microwave meta-skin, with clocking effects from 8-13 GHz and an effective medium ratio of six [5]. In 2016, Du et al presented a left-handed metamaterial created by the combination of ferrite sheets and dielectric rods to investigate the electromagnetic properties for X-band applications [20].…”
Section: Introductionmentioning
confidence: 99%
“…The dimensions of the designed meta-atom are 10 × 10 mm 2 , which is compact in size according to the effective medium ratio and comparison with [5,17,19,[21][22][23]. The proposed meta-atom unit cell and arrays also exhibit more frequency bands with a wider bandwidth than [1, 4,5,16,17,[19][20][21][22][23]. Moreover, the proposed meta-atom is used for enhancing the antenna bandwidth, number of frequency bands and gain because the number of frequency bands, bandwidth and gain of the antenna can be improved by using the partial or slotted or fractal or meta-atom integrated ground plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From Table 8, the bandwidth of the designed meta atom is 3.70 GHz, which is almost threefold of that in [8]. However, the bandwidth has increased by almost 12.16%, 61.89%, 28.38%, and 58.64% of those in [9], [10], [11], and [12], respectively. …”
Section: Parametric Studies Analysismentioning
confidence: 97%
“…the bandwidths cover 3.70 GHz and 2.22 GHz, respectively. The proposed meta-atom unit cell shows a larger bandwidth than the reference prototypes [8][9][10][11][12] and exhibits double negative characteristics of the resonance frequency. Besides, here a parametric study has been performed to demonstrate the effects of inductance and capacitance on resonance frequencies.…”
mentioning
confidence: 99%